Peer Tutoring with Realistic Mathematics Education in Inclusive Class to Improve Problem-Solving Skills - Putranto, Sumbaji; Marsigit, Marsigit; Ratnasari, Gamarina Isti (LPPM Undiksha, 2022)
Many teachers are unprepared to teach special-needs students in inclusive classes. In addition, methods and approaches related to the effectiveness of learning mathematics in inclusive classes have not been explored, especially those related to problem-solving skills. This study aims to analyze the effectiveness of the peer tutoring method with the Realistic Mathematics Education approach to the problem-solving skills of slow learners and inclusive class students. This type of research is a quasi-experimental design with a Group Pretest-Posttest design. The sample of this study was selected by saturated sampling consisting of 31 slow learners and 62 regular students spread over three inclusive classes. Determination of slow learners is based on the results of intelligence tests and student learning outcomes. The instrument used to measure problem-solving skills is an essay in the form of a pretest and posttest. The data analysis technique is descriptive qualitative, quantitative, and inferential analysis. The results showed that the average post-test score was higher than the average pretest score based on problem-solving skills, more than 75% of all students. Get a score higher than the minimum achievement criteria. It shows that the peer tutoring method with the Realistic Mathematics Education approach is effectively applied in inclusive classes for slow learners and general students regarding problem-solving skills.